Synthesis and anticancer activity of dimeric podophyllotoxin derivatives - Zi C; Yang L; Xu F; Dong F; Yang D; Li Y; Ding Z; Zhou J; Jiang Z; Hu J (Dove Medical Press, 2018)
Cheng-Ting Zi,1–3,* Liu Yang,2,* Feng-Qing Xu,2 Fa-Wu Dong,2 Dan Yang,2 Yan Li,2 Zhong-Tao Ding,3 Jun Zhou,2 Zi-Hua Jiang,4 Jiang-Miao Hu2 1Key Laboratory of Pu-er Tea Science, Ministry of Education, College of Science, Yunnan Agricultural University, Kunming 650201, China; 2State Key Laboratory of Phytochemistry and Plant Resources in West China, Kunming Institute of Botany, Chinese Academy of Sciences, Kunming 650201, China; 3Key Laboratory of Medicinal Chemistry for Nature Resource, Ministry of Education, School of Chemical Science and Technology, Yunnan University, Kunming 650091, China; 4Department of Chemistry, Lakehead University, Thunder Bay, ON P7B 5E1, Canada *These authors contributed equally to this work Background: Podophyllotoxin is a potent cytotoxic agent and serves as a useful lead compound for the development of antitumor drugs. Several podophyllotoxin-derived antitumor agents, including etoposide, are currently in clinical use; however, their therapeutic efficacy is often limited due to side effects and the development of resistance by cancer cells. Previous studies have shown that 4β-1,2,3-triazole derivatives of podophyllotoxin exhibit more potent anticancer activity and better binding to topoisomerase-II than etoposide. The effect of dimerization of such derivatives on the anticancer activity has not been studied. Methods: Two moieties of podophyllotoxin were linked at the C-4 position via 1,2,3-triazole rings to give a series of novel dimeric podophyllotoxin derivatives. 4β-Azido-substituted podophyllotoxin derivatives (23 and 24) were coupled with various dipropargyl functionalized linkers by utilizing the copper-catalyzed azide-alkyne cycloaddition (CuAAC) reaction to provide dimeric products in very good yield. The in vitro anticancer activity of the synthesized compounds was evaluated by MTT assay against a panel of five human cancer cell lines (HL-60, SMMC-7721, A-549, MCF-7, and SW480). The normal BEAS-2B (lung) cell line was also included for study in order to evaluate the cancer selectivity of the most active compound as compared with normal cells. Results: A group of 16 dimeric podophyllotoxin derivatives with different linkers were synthesized and structurally characterized. Most compounds do not show significant cytotoxicity (IC50 > 40 mM) against all five cancer cell lines. However, one compound (29) which bears a perbutyrylated glucose residue on the glycerol linker is highly potent against all five cancer cell lines tested, with IC50 values ranging from 0.43 to 3.50 µM. This compound (29) also shows good selectivity towards cancer cell lines as compared with the normal BEAS-2B (lung) cell line, showing selectivity indexes from 4.4 to 35.7. Conclusion: The anticancer activity of dimeric podophyllotoxin derivatives is generally speaking not improved as compared to their monomeric counterparts, and the potency of these dimeric derivatives can be largely affected by the nature of the linker between the two moieties. Among the synthesized derivatives, compound 29 is significantly more cytotoxic and selective towards cancer cells than etoposide and cisplatin, which are currently in clinical use. Compound 29 is a promising anticancer drug and needs further studies. Keywords: podophyllotoxin, dimeric podophyllotoxin derivatives, CuAAC reaction, perbutytylated glucose, antitumor, synthesis